\(\frac{5}{3}+\frac{5}{6}-x=\frac{2}{9}\)
\(\frac{30}{18}+\frac{15}{18}-x=\frac{4}{18}\)
\(x=\frac{30}{18}+\frac{15}{18}-\frac{4}{18}\)
\(x=\frac{41}{18}\)
\(\frac{5}{3}+\frac{5}{6}-x=\frac{2}{9}\)
\(\frac{30}{18}+\frac{15}{18}-x=\frac{2}{9}\)
\(\frac{45}{18}-x=\frac{2}{9}\)
\(x=\frac{45}{18}-\frac{2}{9}\)
\(x=\frac{45}{18}-\frac{4}{18}\)
\(x=\frac{41}{18}\)
Vậy \(x=\frac{41}{18}\)
\(\frac{5}{3}+\frac{5}{6}-x=\frac{2}{9}\)
\(\frac{30}{18}+\frac{15}{18}-x=\frac{4}{18}\)
\(x=\frac{30}{18}+\frac{15}{18}-\frac{4}{8}\)
\(x=\frac{41}{18}\)
học tốt
5/3 + 5/6 - x = 2/9
15/6 - x = 2/9
x = 15/6 - 2/9
x = 41/18